2019
DOI: 10.3389/fneur.2019.00965
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Therapy for Concurrent Cardio-Cerebral Infarction in a Patient With Trousseau Syndrome

Abstract: Only a few patients have been reported to undergo endovascular therapy for Trousseau syndrome. This is the first report of a patient with Trousseau syndrome who developed synchronous cardiocerebral infarction and underwent endovascular therapy for both. A 55-year-old woman with Trousseau syndrome arising from stage IV ovarian cancer presented with consciousness disturbance, aphasia, and right hemiparesis. Magnetic resonance imaging showed acute cerebral infarction limited to the left basal ganglia and occlusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…13,14) In these studies, risk factors of re-occlusion included the number of device passes, missed residual thrombus or stenosis on the past angiography after thrombectomy, intracranial ICA or M2 occlusion, stroke of undetermined cause, and statin pretreatment. 13,14) According to our research, there are 14 reported incidences of TS treated by MT with available literature [2][3][4]13,[15][16][17][18][19][20][21][22] (Table 1). Of half of the cases that experienced re-occlusion of the cerebral large vessels, five cases involved the same vessels.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…13,14) In these studies, risk factors of re-occlusion included the number of device passes, missed residual thrombus or stenosis on the past angiography after thrombectomy, intracranial ICA or M2 occlusion, stroke of undetermined cause, and statin pretreatment. 13,14) According to our research, there are 14 reported incidences of TS treated by MT with available literature [2][3][4]13,[15][16][17][18][19][20][21][22] (Table 1). Of half of the cases that experienced re-occlusion of the cerebral large vessels, five cases involved the same vessels.…”
Section: Discussionmentioning
confidence: 97%
“…Sakuta et al reported cerebral LVO with acute myocardial infarction (AMI) in TS. 15) After successful endovascular therapy for both arteries, Fig. 4 Coronary angiography showing occlusion of the left anterior descending branch (A).…”
Section: Discussionmentioning
confidence: 99%
“…The second important point of this case is endovascular treatment. In general, endovascular treatment is rare in ischemic brain infarctions associated with Trousseau syndrome (Sakuta, Mukai, Fujii, Makita, & Yaguchi, 2019). The reasons are activity of daily living(ADL), location of stroke, time from onset, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…3) There are now multiple reports of mechanical thrombectomy for Trousseau's syndrome; however, recurrent thrombectomy for stroke is uncommon. [3][4][5][7][8][9][10] In two large series, recurrent thrombosis was reported at about 2%, although not all of these received repeat intervention. 6,11) These series differ on their impression of the impact of recurrent thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…TICI 2b recanalization was achieved. 7) Following the third thrombectomy, the patient had residual expressive aphasia but retained the ability to answer "yes/no questions" and to ambulate. He was discharged to home on POD 10, on aspirin and clopidogrel to prevent stent thrombosis, and full-dose enoxaparin for systemic anticoagulation.…”
Section: Case Reportmentioning
confidence: 96%